PENGARUH ESG TERHADAP KINERJA KEUANGAN DENGAN MODERASI KEKUATAN CEO PADA PERUSAHAAN BEI - Widya Oktavia; Dewi Anggraini; Arisky Andrinaldo (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
This study aims to analyze the influence of environmental performance, social performance, and governance performance on financial performance with CEO power as a moderating variable. This research is a quantitative study using secondary data. Twelve manufacturing companies were selected through purposive sampling using predetermined criteria. The data analysis method used was panel data regression using Eviews 13. The results of this study indicate that the performance environmental, social performance, and governance performance simultaneously (f-test) has an effect on financial performance (ROA). Partially (t-test) environmental performance does not have a significant effect on financial performance (ROA), social performance does not have a significant effect on financial performance (ROA), and governance performance has a significant effect on financial performance (ROA). However, the results of the model equation test panel data regression (MRA) CEO power (CEO education) weakens or cannot moderate the influence of environmental performance on financial performance (ROA), CEO power (CEO education) strengthens or can moderate the influence of social performance on financial performance (ROA), and CEO power (CEO education) weakens or cannot moderate the influence of governance performance on financial performance (ROA).